Analysis of Health Polytechnic Semarang Needs Leading to World Class University - Sugiyanto Sugiyanto; Marsum Marsum; Lanny Sunarjo (Jurnal LINK, 2013)
Health Polytechnic Semarangimplemented quality assurance system in the management of continuing education in the hope of polytechnic universities able to become qualified, meets National Education Standards, define and realize its vision through the implementation of its mission and meet the needs of stakeholders to pursue even higher at World Class University. Onlyinstitutions thatgiveattention toquality andcustomer satisfactionthatcan surviveand winthe competition. The purposeof this studywas to determine thereadiness ofresources (human, material, methods andmanagement)andwhat the needs of Health PolytechnicSemarangleadingWorld ClassUniversity.This research is a descriptive research (quantitative), survey method approach to the study. Subjects were academic civitas of The Health PolytechnicSemarang in 2012 including educational staff (271 people), teaching staff (254 people) and students (1320 people) with a total sampling technique. The research instrument used was a questionnaire and a list of questions as well as secondary data. Results from the questionnaires, interviews and secondary data analyzed and evaluated by the frequency distribution. The results shows that the readiness of resources until the year 2012 is 45.83%, while the Health PolytechnicSemarang needs leading to WCU include preparation of the road map in short-term (2012 to 2016), medium (2017 to 2025) and long-term ( 2026 - 2040) and the preparation of the activities or programs to support the implementation of the road map for the short term. Required monitoring and evaluation of short-term road map.